Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1.VP\)
\(\left(a+b\right)^2-2ab=a^2+2ab+b^2-2ab\)
\(=a^2+b^2=VT\left(DPCM\right)\)
1/ (a + b)2 - 2ab = a2 + 2ab + b2 - 2ab = a2 + b2 + (2ab - 2ab) = a2 + b2
2/ (a2 + b2)2 - 2a2b2 = a4 + 2a2b2 + b4 - 2a2b2 = a4 + b4 + (2a2b2 - 2a2b2) = a4 + b4
\(a^6+a^4+a^2b^2+b^4-b^6\)
\(=\left(a^6-b^6\right)+\left(a^4+a^2b^2+b^4\right)\)
\(=\left(a^2-b^2\right)\left(a^4+a^2b^2+b^4\right)+\left(a^4+a^2b^2+b^4\right)\)
\(=\left(a^4+a^2b^2+b^4\right)\left(a^2-b^2+1\right)\)
\(=\left[a^4+2a^2b^2+b^4-a^2b^2\right]\left(a^2-b^2+1\right)\)
\(=\left[\left(a^2+b^2\right)^2-\left(ab\right)^2\right]\left(a^2-b^2+1\right)\)
\(=\left(a^2-ab+b^2\right)\left(a^2+ab+b^2\right)\left(a^2-b^2+1\right)\)
Chúc bạn học tốt.